Rancang Bangun E-Commerce Penjualan Dan Pemesanan Cake pada Yandhi Bakery dengan Codeigniter - Evrilian, Yandhi; Santoso, Dwi Budi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Yandhi bakery is a company engaged in the business of selling bread in the city of Pati. Yandhi bakery business development is not too significant because the sales and ordering system at Yandhi bakery still relies on direct interaction with customers. Moreover, during the current pandemic, large-scale social restrictions are also one of the obstacles in sales. So that makes it difficult for the customer to make transactions with the Yandhi bakery. With the economy not being so good because there is no significant increase in sales, it requires this business to try online business opportunities through the use of E-commerce. This research was conducted to design and build e-commerce sales and orders at Yandhi bakery in order to facilitate the transaction process. Website development uses the Codeigniter 3 framework which is one of the php frameworks. The result of this research is to facilitate the transaction process between the customer and yandhi bakery, customers can place orders anywhere and anytime without having to come directly to the yandhi bakery store